Promising Pharmacological Directions in the World of Lysophosphatidic Acid Signaling - Stoddard, Nicole C. (Biomol Ther (Seoul), 2015)
Lysophosphatidic acid (LPA) is a signaling lipid that binds to six known lysophosphatidic acid receptors (LPARs), named LPA(1)-LPA(6). These receptors initiate signaling cascades relevant to development, maintenance, and healing processes throughout the body. The diversity and specificity of LPA signaling, especially in relation to cancer and autoimmune disorders, makes LPA receptor modulation an attractive target for drug development. Several LPAR-specific analogues and small molecules have been synthesized and are efficacious in attenuating pathology in disease models. To date, at least three compounds have passed phase I and phase II clinical trials for idiopathic pulmonary fibrosis and systemic sclerosis. This review focuses on the promising therapeutic directions emerging in LPA signaling toward ameliorating several diseases, including cancer, fibrosis, arthritis, hydrocephalus, and traumatic injury.